Aktualisasi Diri Tokoh Utama dalam Novel “Represi” Karya Fakhrisina Amalia Kajian Psikologi Sastra - Ika Sartika; Muhammad Rapi; Suarni Syam Saguni (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. This study aims to describe the main character's self-actualization in the novel Represi by Fakhrisina Amalia using Abraham Maslow's psychological study. This type of qualitative research is descriptive. The data source for this research is the novel Repression by Fakhrisina Amalia which is published by PT Gramedia Pustaka Utama, Jakarta. The data in this study are text in the form of words or sentences that show the conflict and self-actualization of the characters in the novel Represi by Fakhrisina Amalia. The data collection technique in this research is the literature study technique. The data in the study were analyzed using data reduction, data presentation, and drawing conclusions. The results of this study indicate that the characteristics in achieving actualization include being able to see reality efficiently, accepting oneself and others as they are, spontaneity, simplicity, and fairness, being focused on problems, requiring solitude, autonomy, independence from culture and the environment, freshness and appreciation. sustainability, social awareness, interpersonal relationships, democracy, a sense of meaningful and ethical humor, creativity, independence and the presence of peak experiences. Keywords: Novel, actualization, humanistic psychology.